2017
DOI: 10.1080/00016489.2017.1384059
|View full text |Cite
|
Sign up to set email alerts
|

Will the presence of the patient at multidisciplinary meetings influence the decision in head and neck oncology management?

Abstract: The presence of the patient during MTMs is not essential if the files are thoroughly presented and discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…In general, healthcare providers fear attendance would increase anxiety, undermine the doctor-patient relationship (through complex discussions in jargon with different viewpoints put forward by the attending professionals) and have a negative impact on the dynamics of the meeting [ 22 ]. The effect of the presence of the patient during the MDTM, including physical examination, did not change the therapeutic decision in a prospective study among 119 head and neck cancer patients [ 60 ]. From a patient’s point of view, increased anxiety or depression due to MDTM participation was not noted in most studies, while being better informed and able to present their own preferences were named as advantages [ 20 , 23 , 24 , 27 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, healthcare providers fear attendance would increase anxiety, undermine the doctor-patient relationship (through complex discussions in jargon with different viewpoints put forward by the attending professionals) and have a negative impact on the dynamics of the meeting [ 22 ]. The effect of the presence of the patient during the MDTM, including physical examination, did not change the therapeutic decision in a prospective study among 119 head and neck cancer patients [ 60 ]. From a patient’s point of view, increased anxiety or depression due to MDTM participation was not noted in most studies, while being better informed and able to present their own preferences were named as advantages [ 20 , 23 , 24 , 27 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…The effect of the presence of the patient during the MDTM, including physical examination, did not change the therapeutic decision in a prospective study among 119 head and neck cancer patients [ 60 ]. From a patient’s point of view, increased anxiety or depression due to MDTM participation was not noted in most studies, while being better informed and able to present their own preferences were named as advantages [ 20 , 23 , 24 , 27 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…For future research, we strongly recommend defining and differentiating the unit of analysis by breaking it down into the recommendation or decision. This might explain divergent results concerning the need for MTCpp: While Massoubre et al 36 found that 97% of MTC recommendations without patient participation were followed and concluded that MTCpp is not essential, Hollunder et al found a great lack of MTC decision adherence caused by missing patient information and failure to consider their preferences 23 which might increase the need for MTCpp, even in the case of limited clinical evidence 53 or limited multidisciplinary discussion. 54,55 For future research, this should firstly mean that patient outcomes have to be analyzed as they are an important part of general MTC outcome quality.…”
Section: Discussionmentioning
confidence: 99%
“…Our results confirm previous findings from international research concerning providers' views on MTCpp. [34][35][36][37]51 Butow et al 2007 reported providers mentioning potential patient anxiety during and after the MTC as well as a conflict between medical and lay language. 35 We can expand Butow's findings concerning the management of patient involvement by describing variations of MTCpp: Patients may enter the MTC after the medical discussion, a smaller MTC setting may be implemented, and patients may be supported by a breast care nurse before, during and after the meeting.…”
Section: Feasibility Of Mtc Patient Participationmentioning
confidence: 99%
See 1 more Smart Citation